Willingness to pay for quality traits and implications for sweetpotato variety breeding: case of Mozambique - Mulwa, C.K.; Tomo, A.; Mudema, J.; Makunde, G.S.; Andrade, M.I.; Ssali, R.T.; Abdul, N.; Campos, Hugo (International Potato Center, 2023)
Despite decades of research and dissemination of improved sweetpotato varieties, uptake at scale remains low and envisaged development goals of food security and livelihoods remain elusive. This is despite demonstrated impacts of such technologies in combating food and nutrition insecurity, amidst global challenges like climate change. Growing evidence show that end-user acceptance of improved varieties is critical in the widespread adoption of such varieties, and inclusion of the heterogenous preferences of diverse sets of end-users in the variety development process is therefore critical. With global changes in weather and consumption patterns, end-users are now demanding varieties that are more suitable to their unique consumption needs, production environments, new market demands and have desired processing characteristics. Such dynamics in demand have necessitated rethinking of breeding programs from the traditional focus on agronomic gains such as increase in yields and yield protection, to consideration of more nuanced quality-related traits that appeal to targeted populations.